The politics of security reform in post-2011 Tunisia: assessing the role of exogenous shocks, domestic policy entrepreneurs and external actors. Issue 2 (4th March 2019) - Hanau Santini, Ruth; Cimini, Giulia
Abstract: In post—2011 Tunisia, the reform of the security sector has proceeded haphazardly, hindering security efficiency and lowering the overall effectiveness in countering threats. Since 2015, the combination of three factors — external shocks, international actors' pressures and domestic configurations of political power — have paved the way for a progressive overhaul of the efficiency of security agencies. Following the 2015 terrorist attacks, that destabilized the political system and risked derailing the trajectory of democratic consolidation, European powers exerted pressure to improve efficiency in the security sector. Lastly, these push factors needed an enabling condition, a strong presidency of the republic, to make the changes happen. The measures adopted reflect a technical and supposedly depoliticized view of reforms, in line with a broader post‐interventionist trend in Security Assistance. Based on process-tracing, the analysis of primary documents and several in‐depth interviews carried out between 2015 and 2017, the article illustrates the workings of the policy process in the security arena. It sheds light on the conditions that made possible the adoption of reforms, the role external actors played in pushing for change and in creating a new multilateral mechanism, the G7+, which produced an unintended set of domestic consequences.